Actuator Fault Tolerant Control of Variable Pitch Quadrotor Vehicles. Issue 2 (2020) - Baldini, Alessandro; Felicetti, Riccardo; Freddi, Alessandro; Longhi, Sauro; Monteriù, Andrea
Abstract: Variable pitch quadrotors can experience actuation faults and failures of two main types: one type related to the rotor system and the other one related to the blade pitch servo. In this paper, we face the fault tolerant attitude tracking problem for a variable pitch quadrotor, in case of partial loss of effectiveness of the rotor system or lock-in-place of the blade pitch servo. The proposed solution is based on the combination of the Disturbance Observer Based Control design paradigm together with that of Active Fault Diagnosis. In detail, an observer is designed for estimating the thrust produced by each rotor. An active diagnosis scheme is adopted to discriminate which fault/failure is affecting the system. Finally, a control allocation algorithm solves the optimal redistribution problem of the control effort among the rotors, subject to different constraints. The proposed overall optimal fault tolerant control scheme can be coupled with most of the nonlinear control laws commonly applied to conventional, fixed pitch, quadrotor systems. Numerical simulations show the capability of the proposed scheme to handle both loss of effectiveness of the rotor system or lock-in-place of the blade pitch servo.